2018
DOI: 10.1158/1535-7163.mct-18-0037
|View full text |Cite
|
Sign up to set email alerts
|

Novel Trifluoromethylated Enobosarm Analogues with Potent Antiandrogenic Activity In Vitro and Tissue Selectivity In Vivo

Abstract: Prostate cancer often develops antiandrogen resistance, possibly via androgen receptor (AR) mutations, which change antagonists to agonists. Novel therapies with increased anticancer activity, while overcoming current drug resistance are urgently needed. Enobosarm has anabolic effects on muscle and bone while having no effect on the prostate. Here, we describe the activity of novel chemically modified enobosarm analogues. The rational addition of -trifluoromethyl groups into ring B of enobosarm, profoundly mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…[10][11][12] Previously, we have found that the introduction of 3,5-bis-trifluoromethyl (3,5-bis-CF3) substituents into ring B of bicalutamide, enobosarm and umbelliferone derivatives, has profoundly modified their anti-proliferative activity, pharmacokinetic and tissue distribution profiles by providing the geometric bulk needed to keep ring B towards Helix 12 while keeping the crucial interactions of the nitrile/nitro group of ring A with Arg 752. [13][14][15] Noting that both flutamide and darolutamide (ODM-201) are lacking the linker OH group, Figure 1, in this work we studied whether the central hydroxyl group of bicalutamide is necessary for maintaining the anti-androgen activity and if the successive increase in the bulk size of ring B substituents (from 4-F  4-CF3  3,5-bis-CF3) would compensate for the smaller size of the deshydroxy linker (lacking the central OH group). We used four different variations of aromatic ring A ( Figure 3); all containing the necessary 4-CN or 4-NO2 for the interaction with Arg 752 in addition to either 2-CF3 or 3-CF3 substituent to understand better the structure activity relationship.…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12] Previously, we have found that the introduction of 3,5-bis-trifluoromethyl (3,5-bis-CF3) substituents into ring B of bicalutamide, enobosarm and umbelliferone derivatives, has profoundly modified their anti-proliferative activity, pharmacokinetic and tissue distribution profiles by providing the geometric bulk needed to keep ring B towards Helix 12 while keeping the crucial interactions of the nitrile/nitro group of ring A with Arg 752. [13][14][15] Noting that both flutamide and darolutamide (ODM-201) are lacking the linker OH group, Figure 1, in this work we studied whether the central hydroxyl group of bicalutamide is necessary for maintaining the anti-androgen activity and if the successive increase in the bulk size of ring B substituents (from 4-F  4-CF3  3,5-bis-CF3) would compensate for the smaller size of the deshydroxy linker (lacking the central OH group). We used four different variations of aromatic ring A ( Figure 3); all containing the necessary 4-CN or 4-NO2 for the interaction with Arg 752 in addition to either 2-CF3 or 3-CF3 substituent to understand better the structure activity relationship.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we generated bicalutamide and enzalutamide-resistant clones of the LNCaP and VCaP cell lines, as tools for screening novel AR-antagonist compounds (10, 11). The VCaP BicR / EnzR -resistant clones showed resistance to both bicalutamide and enzalutamide – showing cytostatic effects at high doses.…”
Section: Introductionmentioning
confidence: 99%
“…Pten loxp/loxp ;Pb-Cre4 mice (The Jackson Laboratory, Bar Harbour, ME, USA), which have prostate-speci c PTEN deletion 62 , were treated with 50 mg/kg Enzalutamide (in 5% DMSO +1% CMC +0.1% P80 oral gavage) or vehicle control every day for three days. All work was carried out in accordance with the provisions of the Animals (Scienti c Procedures) Act 1986 of the United Kingdom.…”
Section: Mouse Studiesmentioning
confidence: 99%